2021
DOI: 10.1155/2021/8870615
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of an Exercise Training Program on Physical Functioning and Quality of Life in Pulmonary Hypertension: A Randomized Controlled Trial

Abstract: The aim of this study was to evaluate the effects of a 6-month combined aerobic and strength exercise training program on functional and psychological aspects and health-related quality of life in patients with PH and to evaluate its longer-term impact. In total, 22 stable patients (mean age 53.9 ± 13.8 , 13 female) with pulmonary hypertension of World Health Organization (WHO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Ehlken et al [21] reported their RCT with peak VO 2 as the primary endpoint that after 15 weeks of ERT, the 6MWD and peak VO 2 of the training group were significantly improved compared with the control group. The results of this study are consistent with most other studies [15,22,25,27,32,35,37,50]. In addition, Ehlken et al also invasively measured the haemodynamic changes of studied patients by RHC.…”
Section: The Effect Of Ert On the Functional And Physiological Factorssupporting
confidence: 92%
See 4 more Smart Citations
“…Ehlken et al [21] reported their RCT with peak VO 2 as the primary endpoint that after 15 weeks of ERT, the 6MWD and peak VO 2 of the training group were significantly improved compared with the control group. The results of this study are consistent with most other studies [15,22,25,27,32,35,37,50]. In addition, Ehlken et al also invasively measured the haemodynamic changes of studied patients by RHC.…”
Section: The Effect Of Ert On the Functional And Physiological Factorssupporting
confidence: 92%
“…Recently, two ERT studies lasting 6 months were designed aiming to evaluate the long-term effects of ERT on PH. Studies have shown that after 6 months of combined aerobic and strength training, the physical function of the patients as reflected by the 6MWD, lower limb strength, CPET variables, and mental health scores have been significantly improved compared with the control group [20], and these beneficial results were still maintained 3 months after the termination of the ERT [25]. In follow-up, the survival rate in the first 2 years for these patients with PH was 100% and 95%, respectively [50].…”
Section: The Effect Of Ert On Ph In the Long Termmentioning
confidence: 99%
See 3 more Smart Citations